The effect of leisure engagement on preschool teachers’ job stress and sustainable well-being - Nong, Liying; Wu, Yu-Feng; Ye, Jian-Hong; Liao, Chen; Wei, Changwu (Frontiers in Psychology, 2022)
The preschool education profession often faces many challenges and preschool teachers, as important members of the preschool education profession must respond to a variety of emergencies with young children, which also leads to high levels of job stress and can have a negative impact on their ongoing well-being. Past research has pointed out that a healthy lifestyle is one of the key factors in enhancing sustainable well-being in high-stress work situations and many studies have found that good leisure activity engagement as a healthy lifestyle is associated with higher levels of well-being. However, the relationship between preschool teachers’ leisure engagement and sustainable well-being has been less explored. Therefore, this study proposed seven research hypotheses based on the engagement theory proposed by Fredricks et al. (2004) and developed a research model to explore the relationship between three types of leisure engagement, including behavioral, affective and cognitive, and preschool teachers’ job stress and sustainable well-being, using age as a control variable. This study used a cross-sectional web-based questionnaire with a convenience sample of 500 preschool teachers in China. The collected data were analyzed for reliability and validity, model fit testing and structural equation modeling for model validation after removing invalid data and incomplete responses. The results of the study showed that (a) behavioral engagement was not related with either the job stress or sustainable well-being of preschool teachers; (b) Emotional and cognitive engagement were negatively related to job stress but positively related to the sustainable well-being of preschool teachers; and (c) Job stress was negatively related to the sustainable well-being of preschool teachers; (d) Age is an effective control variable. From the above results, it is clear that not all three types of leisure engagement are effective in terms of reducing the work stress of preschool teachers. As well as being related to the sustainable well-being of preschool teachers emotional and cognitive engagement contributed more to sustainable well-being acquisition.